Pengaruh Motivasi Belajar Dan Kreativitas Melalui Kemandirian Belajar Sebagai Variabel Mediasi Terhadap Hasil Belajar Korespondensi Mahasiswa Pendidikan Administrasi Perkantoran Angkatan 2022 Universitas Negeri Semarang - Putri, Eviana Lestari; Tusyanah, Tusyanah (Universitas Negeri Semarang, 2024)
This study aims to analyze the effect of learning motivation and creativity through learning independence as a mediating variable on correspondence learning outcomes of office administration education students class of 2022, Universitas Negeri Semarang. The population used in the study were office administration education students class of 2022 who took correspondence courses as many as 131 students. this study used data collection techniques with unstructured interviews and questionnaires and data analysis techniques using SEM-PLS. The results showed that learning motivation and creativity had a positive and significant effect directly on self-regulated learning, learning motivation and creativity also had a positive and significant effect directly on correspondence learning outcomes. Self-regulated learning can mediate learning motivation and creativity which have a positive and significant effect on correspondence learning outcomes.